Exploring causal associations of antioxidants from supplements and diet with attention deficit/hyperactivity disorder in European populations: a Mendelian randomization analysis - Chen, Jing; Chen, Lifei; Zhang, Xinguang; Yao, Wenbo; Xue, Zheng (Frontiers in Nutrition, 2024)
Background: Antioxidants from both supplements and diet have been suggested to potentially reduce oxidative stress in individuals with ADHD. However, there is a lack of studies utilizing the Mendelian randomization (MR) method to explore the relationship between dietary and supplemental antioxidants with ADHD.Methods: This study employed two-sample mendelian randomization.Various specific antioxidant dietary supplements (such as coffee, green tea, herbal tea, standard tea, and red wine intake per week), along with diet-derived circulating antioxidants including Vitamin C (ascorbate), Vitamin E (α-tocopherol), Vitamin E (γ-tocopherol), carotene, Vitamin A (retinol), zinc, and selenium (N = 2,603-428,860), were linked to independent single nucleotide polymorphisms (SNPs). Data on ADHD was gathered from six sources, comprising 246,888 participants. The primary analytical method utilized was inverse variance weighting (IVW), with sensitivity analysis conducted to assess the robustness of the main findings.In different diagnostic periods for ADHD, we found that only green tea intake among the antioxidants was significantly associated with a reduced risk of ADHD in males (OR: 0.977, CI: 0.963-0.990, P < 0.001, FDR = 0.065), with no evidence of pleiotropy or heterogeneity observed in the results. Additionally, a nominal causal association was found between green tea intake and childhood ADHD (OR: 0.989, 95% CI: 0.979-0.998, P = 0.023, FDR = 0.843). No causal relationships were detected between the intake of other antioxidant-rich diets and ADHD.Our study found a significant inverse association between green tea intake and male ADHD, suggesting that higher green tea consumption may reduce ADHD risk in males. Further research is needed to explore optimal doses and underlying mechanisms.